Adapting the ACMG/AMP variant classification framework: A perspective from the ClinGen Hemoglobinopathy Variant Curation Expert Panel. Issue 8 (24th September 2021) - Kountouris, Petros; Stephanou, Coralea; Lederer, Carsten W.; Traeger‐Synodinos, Joanne; Bento, Celeste; Harteveld, Cornelis L.; Fylaktou, Eirini; Koopmann, Tamara T.; Halim‐Fikri, Hashim; Michailidou, Kyriaki; Nfonsam, Landry E.; Waye, John S.; et al.
Abstract: Accurate and consistent interpretation of sequence variants is integral to the delivery of safe and reliable diagnostic genetic services. To standardize the interpretation process, in 2015, the American College of Medical Genetics and Genomics (ACMG) and the Association for Molecular Pathology (AMP) published a joint guideline based on a set of shared standards for the classification of variants in Mendelian diseases. The generality of these standards and their subjective interpretation between laboratories has prompted efforts to reduce discordance of variant classifications, with a focus on the expert specification of the ACMG/AMP guidelines for individual genes or diseases. Herein, we describe our experience as a ClinGen Variant Curation Expert Panel to adapt the ACMG/AMP criteria for the classification of variants in three globin genes ( HBB, HBA2, and HBA1 ) related to recessively inherited hemoglobinopathies, including five evidence categories, as use cases demonstrating the process of specification and the underlying rationale.